Tanatologia powieści Iwana Szmielowa Rok łaskawości Pana. W kręgu wpływu hezychazmu - Kuffel, Józef (Slavia Orientalis, 2025)
The purpose of this article is to hint at an important theme in the émigré works of Ivan Shmelyov, namely the problem of death. The novel The Favorable Year of the Lord (Лето Господне), written in Paris between 1927 and 1948, was basically used as research material. As a landmark for unveiling the function of the thanatological issues in this work, which does not lend itself to a clear genre qualification, we have employed the sketch Old Valaam, published in 1935. In our analysis we will refer to the discourse of synergetic anthropology which, in our opinion, opens up a new perspective in the interpretation of Ivan Shmelyov's legacy. In order to establish a baseline for the analysis of the novel, at the outset it was explained how the hermeneutics of Hesychasm treats the subject of death. The chronotope of the work was then characterized and the origin of the title explained. An important role in determining the role of death in the novel is played by the spiritual guide and confidant of the main character Gorkin. He is the personification of Orthodox piety referring to a certain type of holiness, which has its prototype in biblical figures and the hagiographic figure of St. Sergius of Radonezh. Based on the analysis, it was determined that despite occasional symptoms of Hesychasm direct influence, the indirect influence of this tradition through liturgical practice is revealed.